Exploring EFL Teachers’ Emotion Regulation in Indonesian Classrooms: A Phenomenological Study - Khofifah Novitasari; Basikin Basikin (Journal of Educational Sciences, 2026)
Emotion regulation plays an important role in English as a Foreign Language (EFL) teaching, where instructional responsibilities are often accompanied by emotional demands. This study aimed to explore EFL teachers’ emotion regulation by examining the challenges they encounter, the coping strategies they employ, the regulation practices they enact, and the contextual factors influencing these processes. A qualitative phenomenological approach was employed to capture teachers’ lived experiences in authentic classroom settings. Data were collected through semi-structured interviews and classroom observations involving six EFL teachers from different educational levels. The findings revealed that teachers experienced various emotional challenges, including student disengagement, disruptive behavior, workload pressure, and institutional expectations. To address these challenges, teachers adopted coping strategies such as calming techniques, cognitive reframing, collegial support, and expectation adjustment. These strategies were reflected in emotion regulation practices including situation modification, attentional deployment, cognitive change, and response modulation. The findings also indicated that collegial climate, administrative support, and classroom environment influenced teachers’ emotion regulation. The study concludes that emotion regulation is a dynamic and context-dependent process that contributes to effective teaching practices and teacher well-being.